Analisis Sistem Pemikiran Gender Berbasis Keagamaan di Pesantren Jawa Timur - Mustari Bosra; Umiarso Umiarso; Asyraf Isyraqi bin Jamil (Postgraduate Studies of Universitas Islam Negeri Sunan Ampel Surabaya, Indonesia, 2020)
This research concentrates on the religious-based gender framework within the pesantren education system by which pesantren has an institutional vision to empower women and naturally participates in developing gender discourse with Islamic religious nuance. This research was conducted in East Java by taking the site of Pesantren Nurul Islam Antirogo, Pesantren Al-Falah Karangharjo Jember, and Pesantren Annuqayah Guluk-Guluk Sumenep. This research found that those pesantrens carried out reconstruction through theological-philosophical awareness that was designed from the dialogic process of re-interpretative religious normative texts with reality. The emergence of this awareness led the pesantren to direct their education system to feel egalitarian, non-discriminatory, and non-subordinate towards women inside and outside the pesantren. The axiology of the pesantren education system leads to the normative value of the unity of humanity. The realization of the education system ends up on peace values whether in the cultural, social, or even religious domains.